(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This article presents the changes in the pharmaceutical science of the Republic of Uzbekistan during the years of independence. Initially, problems in pharmaceutical science, their solutions and achievements in this field are presented in this article. In addition, the article highlights the importance of pharmacists in the development of the pharmaceutical industry.